2015
DOI: 10.3171/2014.9.jns131784
|View full text |Cite
|
Sign up to set email alerts
|

Formal protocol for emergency treatment of ruptured intracranial aneurysms to reduce in-hospital rebleeding and improve clinical outcomes

Abstract: OBJECT While the incidence of a recurrent hemorrhage is highest within 24 hours of subarachnoid hemorrhage (SAH) and increases with the severity of the clinical grade, a recurrent hemorrhage can occur anytime after the initial SAH in patients with both good and poor clinical grades. Therefore, the authors adopted a 24-hour-a-day, formal protocol, emergency treatment strategy for patients with ruptured aneurysms to secure the aneurysms as early as possible. The incidences of in-hospital rebleeding and clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 29 publications
1
57
1
2
Order By: Relevance
“…Imaging in the acute phase of SAH presentation may lead to better delineation of the early brain injury caused by SAH. However, MRI is usually not used in the acute phase of SAH as patients require critical care monitoring and MRI requires longer imaging time with minimal clinical monitoring (39, 40). …”
Section: Discussionmentioning
confidence: 99%
“…Imaging in the acute phase of SAH presentation may lead to better delineation of the early brain injury caused by SAH. However, MRI is usually not used in the acute phase of SAH as patients require critical care monitoring and MRI requires longer imaging time with minimal clinical monitoring (39, 40). …”
Section: Discussionmentioning
confidence: 99%
“…Of interest, in a recently published large retrospective comparative cohort study (n=1224), Park et al 29 clearly showed that emergency treatment (median time from admission to start of aneurysm repair 3 hours) was not only associated with a significantly lower rebleeding rate but also with an improved clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the estimated risk of recurrence of 4.1% within 24 hours after the initial rupture, ultra-early treatment of a ruptured aneurysm has been proposed [7]. But on the other hand, the advantages of this strategy are controversial [8], particularly in view of the increased risk of complications during procedures performed in the middle of the night, and also because there is currently no consensus on ultra-early treatment.…”
Section: Indicationsmentioning
confidence: 99%